2015
DOI: 10.1016/j.istruc.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of beam response for progressive collapse analysis

Abstract: A fundamental aspect of the progressive collapse behaviour of building structures is the response of axially restrained beams following partial or total loss of the loadbearing capacity of a supporting member. Owing to the various complex effects involved such as material and geometric nonlinearity, advanced numerical approaches tend to be the most effective tools for modelling performance. Such approaches, however, lack the simplicity needed for common use and may provide only limited capability for understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The flexural capacity of the beams is likely inadequate to solely support the dynamic load, thus mechanisms occur at supports, and alternative resistance paths (e.g., catenary action from frame members or additional retrofit cables) are required to achieve equilibrium and avoid progressive collapse. The transition from flexural resistance to catenary resistance has been observed in experimental work comprising static application of load to structural systems of different materials [13][14][15][16][17][18][19][20][21][22]. The ultimate structural resistance in column removal is a form of catenary behavior that may be available in the frame itself and can also be provided through the use of retrofitted cables.…”
Section: Introductionmentioning
confidence: 99%
“…The flexural capacity of the beams is likely inadequate to solely support the dynamic load, thus mechanisms occur at supports, and alternative resistance paths (e.g., catenary action from frame members or additional retrofit cables) are required to achieve equilibrium and avoid progressive collapse. The transition from flexural resistance to catenary resistance has been observed in experimental work comprising static application of load to structural systems of different materials [13][14][15][16][17][18][19][20][21][22]. The ultimate structural resistance in column removal is a form of catenary behavior that may be available in the frame itself and can also be provided through the use of retrofitted cables.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to rigorous numerical analyses, the model facilitates rapid and quantitative examinations of different alternatives which is an essential component for studying in detail the mechanics of the problem. A separate publication [40] demonstrates how the proposed model can be further exploited as the basis for developing a suitable calculation method for describing the rather complex behaviour of axially restrained beams in progressive collapse.…”
Section: Discussionmentioning
confidence: 99%
“…The nonlinear static response of a single beam system following column removal can be modelled using any suitable software. In order to further simplify the analysis process, an analytical approach that requires only spreadsheet calculations has recently been derived 37 . The method is suitable for analysing the behaviour of the double-span mechanism created by two adjacent beams after removal of their intermediate supporting column as shown in Fig.…”
Section: Analytical Representation Of Beam Nonlinear Static Responsementioning
confidence: 99%
“…The above analytical method is sufficiently rigorous to accurately account for all the essential features of the behaviour such as material nonlinearity, second-order geometry effects, axial-bending interaction and the effects of compressive arching and tensile catenary actions. In particular, verification studies have demonstrated its capability to describe performance to a similar degree of accuracy as detailed finite element models 37 . As compared to those models however, the analytical method offers the advantage of rapid and straightforward applications.…”
Section: Fig 5: Deformations Of Structural Components At the Differementioning
confidence: 99%